Cephalometric Comparison of Wits Appraisal and APP-BPP to the ANB Angle - Silwal, Sanzee; Shrestha, Rabindra Man; Pyakurel, Ujjwal; Bhandari, Sanjeev (Orthodontic Journal of Nepal, 2020)
Introduction: Great emphasis has been given to the evaluation of sagittal apical base relationship in orthodontic diagnosis and treatment planning. Supposedly, the most commonly used parameter is “ANB angle”; however its accuracy and reliability have been questioned. Many authors have alternatively introduced linear parameters like Wits appraisal and APP-BPP. The objective of the study was to compare Wits appraisal and APP-BPP with the ANB angle. Materials & Method: This study was conducted on patients visiting the Department of Orthodontics, Kantipur Dental College, Kathmandu. The sample included 100 lateral cephalograms of subjects of the age group 18–30 years with skeletal Class I relation. Parameters like ANB angle, Wits appraisal and APP-BPP were measured to assess the sagittal jaw relationship. Descriptive statistics were calculated for each parameter. Spearman’s test was done to evaluate the correlation between the parameters. Mann-Whitney U test was done to compare the parameters between male and female subjects. Result: Descriptive statistics showed that the mean values of ANB, Wits appraisal and APP-BPP were 2.26±1.19°, 0.38±0.87mm and 3.25±1.20mm respectively. Mann-Whitney U test showed no significant difference among the parameters between the gender groups (p>0.05). Spearman’s test showed significant correlation among the parameters ANB angle, Wits appraisal and APP-BPP. The parameters had strong positive correlation as r value was greater than 0.7. Conclusion: The strong positive correlation between ANB angle, Wits appraisal and APP-BPP indicates that these parameters can be used as better adjunct to ANB angle in orthodontic diagnosis and treatment planning.